The cross-over from Townes solitons to droplets in a 2D Bose mixture. (1st January 2023) - Bakkali-Hassani, B; Maury, C; Stringari, S; Nascimbene, S; Dalibard, J; Beugnon, J
Abstract: When two Bose–Einstein condensates—labelled 1 and 2—overlap spatially, the equilibrium state of the system depends on the miscibility criterion for the two fluids. Here, we theoretically focus on the non-miscible regime in two spatial dimensions and explore the properties of the localized wave packet formed by the minority component 2 when immersed in an infinite bath formed by component 1. We address the zero-temperature regime and describe the two-fluid system by coupled classical field equations. We show that such a wave packet exists only for an atom number N 2 above a threshold value corresponding to the Townes soliton state. We identify the regimes where this localized state can be described by an effective single-field equation up to the droplet case, where component 2 behaves like an incompressible fluid. We study the near-equilibrium dynamics of the coupled fluids, which reveals specific parameter ranges for the existence of localized excitation modes.